Comparison of Burnout Based on Gender and Part-time Work Among Higher Education Students - Maba, Aprezo Pardodi (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
With an emphasis on gender disparities and part-time employment status, this study explores the causes of burnout among college and university students. The academic world is increasingly concerned about burnout, which is characterized by excessive exhaustion and a loss of interest in academic pursuits. This study, which involved university students from Lampung, Indonesia, indicated that gender is crucial in determining how burnout affects students. Burnout is also more likely when part-time occupations are required due to increased economic hardships. The results highlight the significance of comprehending and resolving the particular difficulties experienced by various student groups in order to promote a supportive learning environment and improve student well-being.